Implementasi Komunikasi Daring dalam Menunjang Jawa Barat sebagai Destinasi Pariwisata Cerdas - Evi Novianti; Shandra Rama Panji Wulung (Jurnal Komunikasi, 2020)
Tourism communication currently tends to be online-based and refers to tourist behavior preferences. West Java as a tourism destination has a variety of online-based tourism communication. This study aims to identify the efforts of the Tourism and Culture Office of West Java in realizing West Java as a smart tourism destination through online communication and the Smiling West Java mobile application. The qualitative method is the approach in this study with primary and secondary data collection. The unit of analysis in this research covers the function of online communication media utilities and components of tourism destinations. This study uses qualitative analysis methods and content analysis methods and is complemented by descriptive qualitative analysis methods through data analysis before going to the field, data reduction, data presentation, and concluding. The efforts of the Tourism and Culture Office of West Java in communicating tourism through three main online media namely websites, social media, and mobile applications. Smiling West Java is a manifestation of smart tourism destinations owned by West Java and provides global scale competitiveness. Komunikasi pariwisata saat ini cenderung berbasis daring dan mengacu kepada preferensi perilaku wisatawan. Jawa Barat sebagai destinasi pariwisata memiliki berbagai komunikasi pariwisata berbasis daring. Penelitian ini bertujuan untuk mengidentifikasi upaya Dinas Pariwisata dan Kebudayaan Provinsi Jawa Barat dalam mewujudkan Jawa Barat sebagai destinasi pariwisata cerdas melalui komunikasi daring dan aplikasi seluler Smiling West Java. Metode kualitatif menjadi pendekatan pada penelitian ini dengan pengumpulan data data primer dan sekunder. Unit analisis dalam penelitian mencakup fungsi utilitas media komunikasi daring dan komponen destinasi pariwisata. Penelitian ini menggunakan metode analisis kualitatif dan metode analisis isi dan dilengkap dengan metode analisis deskriptif kualitatif melalui analisis data sebelum ke lapangan, reduksi data, penyajian data, dan penarikan kesimpulan. Upaya Pemerintah Provinsi Jawa Barat melalui Dinas Pariwisata dan Kebudayaan dalam mengkomunikasikan pariwisata melalui tiga media daring utama yaitu situs web, media sosial, dan aplikasi seluler. Smiling West Java menjadi manifestasi destinasi pariwisata cerdas yang dimiliki oleh Jawa Barat dan memberikan daya saing skala global.